Entomofauna asociada a los detritos de Atta mexicana (F.Smith) (Hymenoptera: Formicidae) en una zona árida del centro de México - Rojas, Patricia (Instituto de Ecología, A.C., 1989)
The leaf-cutting ant Atta mexicana (F. Smith) removes the colony refuse out of the nest, forming typical mounds that attract many animals. The purpose of this work was to study the insects living inthe detritus. Forty nine species belonging in 9 orders were found; Coleoptera constituted 51% of the total number of species, Collembola 16.3% and Diptera 10.2%. According to the developmental stages found in the refuse mounds, three categories were established: permanent, temporal and casual species. The entomofauna is also divided in obligate and facultative inquilines. Seasonal population changes are described taking the mound as a unit and dividing it in three levels. The highest abundance was found in the dry and cool season. Trophic categories are astablished for the entomofauna. The sheiter and food resource roles that detritus play in the area are discussed. The known information on insects associated with Atta refuse mounds is tabulated.